2017
DOI: 10.1177/1359104517712041
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal rejection sensitivity mediates the associations between peer victimization and two high-risk outcomes

Abstract: Interpersonal rejection sensitivity influences the relation between peer victimization and mental health symptoms, including suicidal ideation and aggression. Assessing for and addressing heightened interpersonal rejection sensitivity among adolescents who have been victimized by peers may decrease the likelihood of negative mental health outcomes. Implications, especially for clinicians, are further discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 72 publications
(93 reference statements)
3
9
0
Order By: Relevance
“…The emergence of suicidal ideation is the outcome of a process beginning with feelings of defeat and humiliation. Defeat or humiliation may also be characterized by social rejection and loss, two frequently reported precipitants of suicidal distress [ 2 , 34 36 ]. However, entrapment is not an inevitable consequence of feeling defeated or humiliated.…”
Section: Key Premises Underpinning the Motivational–volitional Model mentioning
confidence: 99%
“…The emergence of suicidal ideation is the outcome of a process beginning with feelings of defeat and humiliation. Defeat or humiliation may also be characterized by social rejection and loss, two frequently reported precipitants of suicidal distress [ 2 , 34 36 ]. However, entrapment is not an inevitable consequence of feeling defeated or humiliated.…”
Section: Key Premises Underpinning the Motivational–volitional Model mentioning
confidence: 99%
“…Rejection sensitivity is defined as the cognitive and emotional tendency to anticipate, perceive, and overreact defensively to the signs of rejection by others [15]. According to the rejection sensitivity model [16], adolescents who suffer from interpersonal rejection tend to experience higher rejection sensitivity and then lead to maladaptive behavioral responses [17,18]. That is to say, rejection sensitivity might mediate the relationship between cybervictimization and Internet addiction.…”
Section: Rejection Sensitivity As a Mediatormentioning
confidence: 99%
“…First, Downey and Feldman [15] demonstrated that the experience of rejection could develop into some form of "basic mistrust" about interpersonal relationships, which leads to higher rejection sensitivity [19,20]. Second, although little study has examined the impact of cybervictimization on rejection sensitivity directedly [17], several studies have indicated that adolescents that often suffer from cyberbullying develop a low social self-perception and make a negative evaluation of their own social ability, which leads to the development of social anxiety [20,21]. At the same time, it has been shown that social anxiety is associated with greater rejection sensitivity [22].…”
Section: Rejection Sensitivity As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…To help understand the true associations between RS and aggression and victimization, this study aimed at revealing a reliable estimate of the effect size using the meta-analytic approach. In addition to that, this study also explored the moderating effects of gender and age on the associations between RS and aggression and victimization on the basis of the significant links of gender and age on those associations (Williams, Doorley, & Esposito-Smythers, 2017; Zimmer-Gembeck et al, 2016). Together, the present study aimed to statistically summarize the association between RS and aggression and between RS and victimization by conducting two meta-analyses.…”
mentioning
confidence: 99%